Flax fiber and its composites: An overview of water and moisture absorption impact on their performance. (April 2019) - Moudood, Abdul; Rahman, Anisur; Öchsner, Andreas; Islam, Mainul; Francucci, Gaston
Contemporary researchers have specified that natural flax fiber is comparable with synthetic fibers due to its unique physical and mechanical characteristics which have been recognized for decades. Flax fiber-reinforced composites have the potential for wide usage in sport and maritime industries, and as automotive accessories. In addition, this composite is in the development stages for future applications in the aeronautical industry. However, designing the flax composite parts is a challenging task due to the great variability in fiber properties. This is caused by many factors, including the plant origin and growth conditions, plant age, location in the stem, fibers extraction method, and the fact that there is often a non-uniform cross section of the fibers. Furthermore, the water and moisture absorption tendency of the flax fibers and their composites and the consequent detrimental effects on their mechanical performance are also major drawbacks. Fibers may soften and swell with absorbed water molecules, which could affect the performance of this bio-composite. Flax fibers' moisture absorption propensity may lead to a deterioration of the fiber–matrix interface, weakening the interfacial strength and ultimately degrading the quality of the composite. This review represents a brief summary of the main findings of research into flax fiber reinforced composites, focusing on the challenges of its water and moisture absorption behavior on their performance.